Protecting civilians in a data-driven and digitalized battlespace: toward a baseline humanitarian technology infrastructure - Fitz-Gerald, Ann; Hennebry, Jenna (Frontiers in Human Dynamics, 2025)
This article examines the realities of modern day warfare, including a rising trend in hybrid threats and irregular warfare which employ emerging technologies supported by digital and data-driven processes. The way in which these technologies become applied generates a widened battlefield and leads to a greater number of civilians being caught up in conflict. Humanitarian groups mandated to protect civilians have adapted their approaches to the use of new emerging technologies. However, the lack of international consensus on the use of data, the public and private nature of the actors involved in conflict, the transnational aspects of the widened battlefield, and the heightened security risks in the conflict space pose enormous challenges for the protection of civilians agenda. Based on the dual-usage aspect of emerging technologies, the challenges associated with regulation and the need for those affected by conflict to demonstrate resilience toward, and knowledge of, digital media literacy, this paper proposes the development of guidance for a "minimum basic technology infrastructure" which is supported by technology, regulation, and public awareness and education